Homoseksual: antara hukum dan kemajuan sains - Binte Batri, Nek Mah (Penerbit UTM, 2016)
Homosexuality is a phenomenon that has ling existed in human history. It is became the targer of the study to find the contri buting factors to the tennets of the Islamic perspec tive. The desire of homosexuals to change the physical conditions of a male to femare or vice versa is a good convention for sexual purposes or desore to become a mother or father status. The pace and progress of science and technology has helped homesexua ls meet their needs, even if the outcome of these treatments may bring much harm to themselves or those around them. High costs of sex change surgeries ca used many homosezual stuck to the nature of adultery and leave a negative impact on health. The purpos e of this paper is to understand the factor that cause homosexuality: Between law and science. The method used is a qualitative approach and a library. The findidngs of the study showd that the f actors that cause the occurrence of homosexuality no only dep end on environmental factors such as parents, peers, social and biological factors, but diet and drugs. There is a lack of research on the different schools of taught concerning the change of gender studies, hence it is has become prevalent in the Muslim c ommunity. If this is not handled as soon as possible, it not only gives an image that is not healthy within our communities but aslo under mine the development of Islamic civilization.